2004
DOI: 10.1111/j.1471-4159.2004.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin–GABA interactions modulate MDMA‐induced mesolimbic dopamine release

Abstract: 3,4,-Methylenedioxymethamphetamine (MDMA; 'ecstasy') acts at monoamine nerve terminals to alter the release and re-uptake of dopamine and 5-HT. The present study used microdialysis in awake rats to measure MDMA-induced changes in extracellular GABA in the ventral tegmental area (VTA), simultaneous with measures of extracellular dopamine (DA) in the nucleus accumbens (NAC) shell. (+)-MDMA (0, 2.5, 5 and 10 mg/kg, i.p.) increased GABA efflux in the VTA with a bell-shaped dose-response. This increase was blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 49 publications
4
54
0
Order By: Relevance
“…Therefore, the elevated levels of mRNA for the GABA A d-subunit in the VTA of FSL rats might be due to an intrinsic GABA-ergic intraneuron modulation (compensation) for low levels of DHEA in this brain region (Concas et al, 1999;Gulinello et al, 2001;Holt et al, 1996;Mahmoudi et al, 1997). The contrasting lower levels of mRNA for the d-subunit in the NAc of FSL compared to SD rats can be explained by different localization of GABA modulation on ascending neurons (Akiyama et al, 2004;Bankson and Yamamoto, 2004;Tao and Auerbach, 2002;Yan et al, 2004). Our results may point to a different role for the GABA A Rs in the NAc compared to the VTA, some of which may be explained by localization of the receptors pre-or post-synaptically (Ikemoto et al, 1997;Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the elevated levels of mRNA for the GABA A d-subunit in the VTA of FSL rats might be due to an intrinsic GABA-ergic intraneuron modulation (compensation) for low levels of DHEA in this brain region (Concas et al, 1999;Gulinello et al, 2001;Holt et al, 1996;Mahmoudi et al, 1997). The contrasting lower levels of mRNA for the d-subunit in the NAc of FSL compared to SD rats can be explained by different localization of GABA modulation on ascending neurons (Akiyama et al, 2004;Bankson and Yamamoto, 2004;Tao and Auerbach, 2002;Yan et al, 2004). Our results may point to a different role for the GABA A Rs in the NAc compared to the VTA, some of which may be explained by localization of the receptors pre-or post-synaptically (Ikemoto et al, 1997;Yan et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…The GABA-ergic system is an important regulator of dopaminergic neurons (Akiyama et al, 2004), which are relevant to depression (Dremencov et al, 2006;Friedman et al, 2007). Specifically, GABA A Rs within the VTA regulate dopamine output to the NAc (Bankson and Yamamoto, 2004;Yan et al, 2004), suggesting a modulatory role for these receptors in depression (Garcia-Alloza et al, 2006). Furthermore, co-administration of a GABA A agonist (muscimol) and DHEA blocked the beneficial effect of DHEA on depressive behavior (Figure 4), confirming that the GABA A R is the main target for DHEA in depression.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed for the nigrostriatal system, these effects may be mediated by actions on GABA cells in the VTA. Intra-VTA administration of the 5-HT2C inverse agonist SB 206553 has been shown both to attenuate MDMA-induced increases in VTA GABA and potentiate the concurrent increase in NA DA (Bankson and Yamamoto, 2004). Likewise, systemic administration of a 5-HT2C agonist has been shown to excite all non-DA, presumably GABAergic cells in the VTA, suggesting that 5-HT2C receptors in this region are localized to GABAergic neurons (Di Giovanni et al, 2001).…”
Section: Mesolimbic Pathwaymentioning
confidence: 99%
“…Several investigators have demonstrated that MDMA produces a marked increase in the extracelllular concentration of DA in the n. accumbens (Cadoni et al, 2005;Kankaanpaa et al, 1998;Marona-Lweicka et al, 1996;Amato et al, 2007;O-Shea et al, 2005;Bankson and Yamamoto, 2004). As in the striatum, MDMA-induced DA release in the n. accumbens appears also to be modulated by 5-HT-GABA interactions.…”
Section: Nucleusmentioning
confidence: 99%
“…As noted above, MDMA-induced suppression of nigral GABA release following 5-HT2A/2C receptor activation disinhibits striatal DA release. However, an MDMA-induced increase in GABA release within the ventral tegmental area (VTA), subsequent to 5-HT2B/C receptor activation, appears to limit the magnitude of MDMAinduced DA release in the n. accumbens (Bankson and Yamamoto, 2004).…”
Section: Nucleusmentioning
confidence: 99%